DESIGN AND IMPLEMENTATION OF A RESONANT WIRELESS POWER TRANSMISSION SYSTEM BASED ON A SELF OSCILATING D.C-A.C CONVERTER (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In the present work a complete wireless power system, composed by two identical units (Transmitter and Receiver) and a Power Electronic Converter (PEC), was designed and built. Receiver unit is constituted of two wire coils, drive coil (DC) and main coil (MC), while transmitter unit have only a MC. In transmitter unit the MC is connected to the PEC. In the receiver unit the DC is connected to a load of 1kÎ© and inductively coupled to the MC. DC has one turn and MC ten turns with 8.3894 ïH. As the natural capacitance of each MC is very small, a capacitor was solder in parallel with each MC to reduce the resonant frequency to about 1.3MHz. The PEC is a self-oscillating DC-AC power converter projected to work in the range from 800kHz to 3MHz.